Synthesis of enantio-pure amides by reversal of the Geobacillus pallidus RAPc8 amidase hydrolysis reaction in non-aqueous media - Gabathuse, Anne Onalethata (Centre for Bioprocess Engineering Research, 2016)
Amidases are hydrolytic enzymes that catalyze the hydrolysis of amides to their corresponding carboxylic acids and ammonia. Amidases are ubiquitous in nature, and they have been isolated from a wide range of microorganisms, the most common source being bacteria. Amidases are recognized as potential industrial biocatalysts in processes that involve the synthesis of chiral compounds, mostly used in the pharmaceutical, agrochemical and food industries. The discovery of amidases from extremophiles has increased the potential for application of these enzymes for the development of new processes. In nonaqueous media, amidases have the ability to synthesize enantiopure amides due to the shift in thermodynamic equilibrium towards synthesis. For synthesis to occur, an acyl donor and an acyl acceptor are required, in which the acyl acceptor acts as a nucleophile. The applicability of amidases in non-aqueous media opens new possibilities for processes in which the enzyme can be used for the industrial synthesis of commercially relevant new products. A novel amidase was previously isOlated from a thermophilic Geobacillus species, and the amidase was cloned and expressed in an Escherichia coli BL21 strain. Also in previous studies, it was shown that the enzyme exhibits both amide hydrolysis and acyl transfer activities. The highest activity of the G. pallidus RAPc8 amidase was observed at 50°C in the presence of acetamide and substrate preference was towards aliphatic, short chain amides. Furthermore, the enzyme displayed enantioselectivity towards lactamide, which is a chiral compound. The amidase compound showed selectivity towards the D-isomer of lactamide and no detectable activity on the L-isomer. This study presents the investigation and development of a novel biocatalytic process that involves the synthesis of enantiopure amides in non-aqueous media, using the G. pal/idus RAPc8 amidase. The amidase was produced and expressed in E. coli BL21.